The Prognostic Significance of Lymphatics in Colorectal Liver Metastases. (20th May 2014) - Muralidharan, Vijayaragavan; Nguyen, Linh; Banting, Jonathan; Christophi, Christopher
Abstract : Background . Colorectal Cancer (CRC) is the most common form of cancer diagnosed in Australia across both genders. Approximately, 40%–60% of patients with CRC develop metastasis, the liver being the most common site. Almost 70% of CRC mortality can be attributed to the development of liver metastasis. This study examines the pattern and density of lymphatics in colorectal liver metastases (CLM) as predictors of survival following hepatic resection for CLM. Methods . Patient tissue samples were obtained from the Victorian Cancer Biobank. Immunohistochemistry was used to examine the spatial differences in blood and lymphatic vessel densities between different regions within the tumor (CLM) and surrounding host tissue. Lymphatic vessel density (LVD) was assessed as a potential prognostic marker. Results . Patients with low lymphatic vessel density in the tumor centre, tumor periphery, and adjacent normal liver demonstrated a significant disease-free survival advantage compared to patients with high lymphatic vessel density (P = 0.01, P > 0.01, andP = 0.05, resp.). Lymphatic vessel density in the tumor centre and periphery and adjacent normal liver was an accurate predictive marker of disease-free survival (P = 0.05 ). Conclusion . Lymphatic vessel density in CLM appears to be an accurate predictor of recurrence and disease-free survival.